Urgensi Peningkatan Akses Layanan Keuangan Bagi Masyarakat Pesisir di Kecamatan Muaragembong Kabupaten Bekasi - Gusganda Suriamanda (Inovasi, 2020)
This study aims to analyze the problems of financial services in such remote areas as Muaragembong Sub-district, as well as various financial service program schemes which allow these coastal communities to access at various business scales. The research method used qualitative analysis with a descriptive approach. There are various alternative financial services for Muaragembong community, which may originate from either the central government or private company programs. The alternative financial services referred to in the study are those in the form of a partnership programs with State-owned Enterprises, Cooperative Revolving Fund Management Institutions, Micro, Small and Medium Enterprises, Maritime and Fisheries Business Capital Management Institutions, and Ultra Micro Finance. The Bekasi Regency Government must take proactive actions in supporting inclusive financial programs to improve the welfare of the coastal communities. This is due to the fact that the implementation of this program is strictly related to the Bekasi Regency's macroeconomic development goals as an effort to reduce poverty and income inequality. This can be implemented through raising and strengthening cooperation with the central government, private sector and other stakeholders. Keywords: financial inclusion, coastal communities, Muaragembong sub-district